Inovasi Produk, Pemasaran Digital sebagai Strategi Pengembangan Bisnis UMKM Kuliner dalam Meningkatkan Daya Saing: (Kecamatan Genuk, Semarang) - Eko Hadi Wahyono; Fransiskus Wandy Syah (Journal of Management and Creative Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy by contributing to local economic development, employment generation, and community welfare. However, increasing market competition and rapid technological advancement require MSMEs to continuously improve their competitiveness through innovation, digital transformation, and sustainable business practices. This study aims to analyze product innovation, digital marketing strategies, and the implementation of Islamic business principles in enhancing the competitiveness of culinary MSMEs in Genuk District, Semarang City. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, and documentation involving culinary MSME owners who had operated their businesses for at least two years. The findings reveal that product innovation has been achieved through menu diversification, the utilization of locally sourced raw materials, and the development of more attractive and modern packaging. Furthermore, business owners have increasingly adopted digital marketing by utilizing social media platforms, online marketplaces, and food delivery applications to expand market reach and improve customer engagement. From the perspective of Islamic business practices, many participants have implemented halal product standards, maintained honesty and transparency in business transactions, and applied fair profit-sharing mechanisms. The integration of product innovation, digital marketing, and Islamic business principles has contributed to increased business revenue, broader market penetration, stronger consumer trust, and improved business sustainability. The study highlights the importance of continuous business mentoring, digital marketing training, and to strengthen the competitiveness of culinary MSMEs at both local and national levels.